The Pharmacognostic Evaluation of Leaves of Medicinal Plants Tephrosia villosaand Cassia Tora (Linn.) - Rani Radhika; begum Tahira (Journal of Advances in Plant Biology, 2021)
Medicinal plants Tephrosia villosaand Cassia tora (Linn.) are belongs to the family Fabaceae and widely distributed in India and other tropical regions. Different parts (roots, stem, leaves and seeds) of the both plants have been used in various traditional medicare systems for ailments of human being. In the present study deals with the evaluation of pharmacognostic parameters in terms of the macro and micro-morphological characters and quantitative profiles of the leaves of Tephrosia villosa andCassia tora(Linn.). The observations of the current study can be useful for identification, standardization and authentication of plants.
Keywords: Macroscopy